Designing a Game To Introduce and Educate Computational Thinking - Millen Dhita; Erdhi Widyarto Nugroho; T. Brenda Chandrawati (Soegijapranata Catholic University, 2024)
To prepare for the industrial era 4.0, the education system in Indonesia needs to change, from only providing learning materials to learning that involves students' ability to think creatively. One way to change this learning system is to implement other learning techniques that hone one's ability to be able to think creatively in solving a problem. One of these learning techniques is Computational Thinking or commonly abbreviated as CT. In Indonesia, Computational Thinking techniques have not been widely used in the teaching and learning process, therefore this research is intended to introduce Computational Thinking learning techniques through game media.